Analisis Pengaruh Model Utaut 2, Trust, dan Perceived Risk Terhadap Behavioral Intention pada Aplikasi Byond By BSI - Nida Auliyah; Osly Usman; Annisa Lutfia (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to identify the factors that influence the interest of Bank Syariah Indonesia (BSI) customers in using the Byond by BSI application, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach. This application is one of the digital innovations developed by BSI to improve digital banking services. The data in this study were obtained from primary data collected directly through a Google Form questionnaire distributed to 290 respondents who are BSI customers and users of the Byond by BSI application. The study employed a non-probability sampling method with purposive sampling technique, where respondents were selected based on specific criteria relevant to the research objectives. Data analysis was conducted through several stages, including descriptive statistics, validity and reliability tests, normality tests, multicollinearity, heteroskedasticity, as well as multiple linear regression analysis and hypothesis testing. Data processing was conducted using SPSS software version 30. The results of the analysis indicate that all variables studied, performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, habit, trust, and perceived risk have a positive and significant influence on behavioral intention or users' interest in continuing to use the Byond by BSI app.